Purchase Intention of SUV Category Automobiles: Determinant Factors from the Customer Perspective - Luciene Eberle; Luan Hoffman da Cruz; Gabriel Sperandio Milan (BBR: Brazilian Business Review)
The study aimed to verify the impact of brand awareness, brand credibility, perceived quality, and perceived innovation as determinants of the intention to purchase SUV automobiles. For this purpose, quantitative research was carried out by applying a survey, with a convenience sample composed of 237 customers intending to purchase SUVs. Multivariate statistics were used to analyze the data through the Structural Equation Modeling approach. The study’s main contributions confirm that brand awareness positively impacts the SUV’s perceived quality, brand credibility, perceived innovation, and purchase intention. Brand credibility directly affects the SUV’s perceived quality. Perceived innovation also influences the SUV’s perceived quality. However, perceived innovation did not positively impact the purchase intention.